2021
DOI: 10.3390/mti5120073
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Domain Knowledge Elicitation in Applied Machine Learning

Abstract: Eliciting knowledge from domain experts can play an important role throughout the machine learning process, from correctly specifying the task to evaluating model results. However, knowledge elicitation is also fraught with challenges. In this work, we consider why and how machine learning researchers elicit knowledge from experts in the model development process. We develop a taxonomy to characterize elicitation approaches according to the elicitation goal, elicitation target, elicitation process, and use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…To achieve this, a documented process of literature search and expert consensus was undertaken to identify, and engineer candidate features and set operational priorities for the intended application. The taxonomy provided by Kerrigan et al ( 7 ) provided a useful framework to represent the elicitation process. In this study, domain knowledge from experts, a literature search and the researcher were integrated to achieve the goals of problem specification and feature selection prior to data collection, feature engineering and pre-processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, a documented process of literature search and expert consensus was undertaken to identify, and engineer candidate features and set operational priorities for the intended application. The taxonomy provided by Kerrigan et al ( 7 ) provided a useful framework to represent the elicitation process. In this study, domain knowledge from experts, a literature search and the researcher were integrated to achieve the goals of problem specification and feature selection prior to data collection, feature engineering and pre-processing.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the integration of human knowledge in a field (domain knowledge) as well as knowledge of learning, the human brain, computer science and statistics (general knowledge) ( 6 ). Kerrigan et al have conducted a survey of the elicitation of domain knowledge in applied machine learning and pointed to the need for the documentation of the elicitation process ( 7 ). In doing so, they have developed a taxonomy for the elicitation process that includes the elicitation goal , the elicitation target , the elicitation process and the use of elicited knowledge .…”
Section: Introductionmentioning
confidence: 99%
“…Applications for machine learning research of this nature, invite close interdisciplinary collaboration that allows the integration of machine learning knowledge with clinical domain knowledge, not only of biomedicine but also of clinical context in a fashion that enhances the relevance and applicability of these new methods. The documentation of these processes can be seen to be an important aspect of rigour when publishing reports of such models and demands the investigation of this agenda ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive metadata about the meaning and data quality is typically not available and metadata management, including data catalogs, is still in the exploration stage [42]. Areas of related research include: domain knowledge elicitation [51], visual domain modeling tools [7], taxonomy development to aid problem specification, feature engineering, model development, and model evaluation [52]. But, studies exploring collaboration tools used in inter-disciplinary teams found that data scientists and domain experts [51], [53] experience adoption challenges because MDATs tend to settle on using tools that everybody is familiar with -rather than expend effort to use expert tools from their own discipline or use new and innovative tools that may be more effective [53].…”
Section: Literature Related To Findingsmentioning
confidence: 99%